Content Analysis Of Educational Genre In "Smart Steps" For The 9th Grade Of Junior High School - Ahmadi, Agus, Prof. Dr. Sri Sumiati, dra.Siti Zuhriah Ariatmi. M.Hum (2013)
This research aims at (1) describing the stages of the text elements of genre, (2) identifying the cohesion and coherence of the reading texts in "Smart Steps" and (3) explaining about the "Smart Steps" textbook compatibility with KTSP curriculum. The research is a qualitative research. The data forms are text and exercise of the text. In collecting data, the writer uses documentation method. The writer takes the data from the "Smart Steps" textbook. After analyzing all the data, the writer finds the elements of genre based on the "Smart Steps". They are: (1) Report: text (1 and 2), (2) Procedure: text (4 and 5), (3) Descriptive: text (6 and 7), (4) Recount: text (3, 8 and 9), (5) Narrative: text (11,12 and 13). The writer finds the cohesion. They are: (1) Substitution: there aren't found substitution in procedure (text 4 and 5) and the exercise of text (6 and 11) aren't found substitution, (2) Ellipsis: there aren't found ellipsis in procedure (text 4 and 5) and the exercise of texts (2,3,4,5,9 and 11) aren't found ellipsis too, (3) Reference: all the texts and the exercises use reference, (4) Conjunction: all the texts use conjunction and all the exercises use conjunction except in the text 2 has no conjunction, (5) Lexical Cohesion: all the texts use lexical cohesion and all the exercises of text use lexical cohesion, in the text (7 and 12) just use lexical cohesion. The writer finds coherence in all of the texts but the exercise in the ( text 2 number 3, 8 number 5 and 9 number 4) aren't coherence. The writer finds the compatibility of the text with the content standard of KTSP curriculum in text (1, 2, 4, 5, 11, 12 and 13). The writer doesn't find the compatibility the text with the content standard of KTSP curriculum in text (3, 6, 7, 8, 9 and 10). Implications of educational are as considering of the education minister to revise the curriculum and introducing cohesion and coherence to 9th grade student of Junior High School.